Answer:
6x^2 -2x
Step-by-step explanation:
As written, the constant terms in the first factor cancel each other. The distributive property is used to perform the multiplication:
(3x^2 +1 -1 -x)(2) = (3x^2 -x)(2) = (3x^2)(2) -x(2)
= 6x^2 -2x
8
46
is equivalent to 4
23
because 4 x 2 = 8 and 23 x 2 = 46
12
69
is equivalent to 4
23
because 4 x 3 = 12 and 23 x 3 = 69
16
92
is equivalent to 4
23
because 4 x 4 = 16 and 23 x 4 = 92
Answer:
90*
Step-by-step explanation:
If you multiply 25×6×4 you should get 600.
hope this helps!
Answer:
Keep the exact order that is shown
Step-by-step explanation:
The first exponential already has a point at (1, -2) which means the y-intercept would be less than -2, which is the lowest among the three
The second has a y-int at -2
Third has y-int at 2